Endothelial-Dependent Vasomotor Dysfunction in Infants After Cardiopulmonary Bypass. Issue 1 (January 2020) - Krispinsky, Luke T.; Stark, Ryan J.; Parra, David A.; Luan, Liming; Bichell, David P.; Pietsch, John B.; Lamb, Fred S.
Abstract : Objectives: Cardiopulmonary bypass–induced endothelial dysfunction has been inferred by changes in pulmonary vascular resistance, alterations in circulating biomarkers, and postoperative capillary leak. Endothelial-dependent vasomotor dysfunction of the systemic vasculature has never been quantified in this setting. The objective of the present study was to quantify acute effects of cardiopulmonary bypass on endothelial vasomotor control and attempt to correlate these effects with postoperative cytokines, tissue edema, and clinical outcomes in infants. Design: Single-center prospective observational cohort pilot study. Setting: Pediatric cardiac ICU at a tertiary children's hospital. Patients: Children less than 1 year old requiring cardiopulmonary bypass for repair of a congenital heart lesion. Intervention: None. Measurements and Main Results: Laser Doppler perfusion monitoring was coupled with local iontophoresis of acetylcholine (endothelium-dependent vasodilator) or sodium nitroprusside (endothelium-independent vasodilator) to quantify endothelial-dependent vasomotor function in the cutaneous microcirculation. Measurements were obtained preoperatively, 2–4 hours, and 24 hours after separation from cardiopulmonary bypass. Fifteen patients completed all laser Doppler perfusion monitor (Perimed, Järfälla, Sweden) measurements. Comparing prebypass with 2–4 hours postbypass responses, there was a decrease in both peak perfusion ( p = 0.0006) and area under the dose-response curve ( p = 0.005) following acetylcholine, but no change in responses to sodium nitroprusside. Twenty-four hours after bypass responsiveness to acetylcholine improved, but typically remained depressed from baseline. Conserved endothelial function was associated with higher urine output during the first 48 postoperative hours ( R 2 = 0.43; p = 0.008). Conclusions: Cutaneous endothelial dysfunction is present in infants immediately following cardiopulmonary bypass and recovers significantly in some patients within 24 hours postoperatively. Confirmation of an association between persistent endothelial-dependent vasomotor dysfunction and decreased urine output could have important clinical implications. Ongoing research will explore the pattern of endothelial-dependent vasomotor dysfunction after cardiopulmonary bypass and its relationship with biochemical markers of inflammation and clinical outcomes. Abstract : Supplemental Digital Content is available in the text.